Politološka refleksija moči v deliberativni demokraciji in njeni agonistični kritiki - Pušnik, Tomaž (Teorija in praksa, 2022)
The paper discusses the understanding of power, a key concept in political science, in the theories of deliberative democracy and their central critique, agonistic democracy. Using Foucault’s approach to power, we show that negative power as coercion and oppression prevails in both a deliberative democracy and in agonism. This means that the theoretical predispositions of a deliberative democracy, by perceiving power as an oppressive force, cannot fully explain the political. Meanwhile, the perception of negative power in agonism prevents the recognition that the ideas and practices of deliberation are already significantly shaping the political
Keywords: agonistika; deliberativna demokracija; politična moč; Politične vede